Geographic distance and board monitoring: Evidence from the relocation of independent directors - Quan, Yi; Zhang, Wenlan (Journal of Corporate Finance, 2021)
In this study, we use a sample of independent directors (hereafter, IDs) in China, whose primary employers have changed during their tenure as IDs, to examine whether and how geographic distance affects the monitoring role of IDs. Based on 233 relocations of IDs due to the change of their primary employers, we find that when IDs are located farther from the firm headquarters, they attend fewer meetings and express a lower percentage of dissenting opinions. The results are robust with a battery of robustness checks. In addition, we find that the negative relationship between geographic distance and meeting attendance of IDs is mitigated where there are high-speed railways between firm headquarters and the ID or when firms have a higher litigation risk. We also find that the negative relationship is more pronounced for state-owned firms. Our tests on the effectiveness of monitoring show that firms with more distant IDs have more tunneling activities and earnings management, lower sensitivity of CEO compensation to firm performance, and lower sensitivity of investment expenditure to investment opportunities. Furthermore, we focus on the relocations that make IDs more distant from the firm headquarters and find that after the relocations, firms are more likely to acquire firms in the provinces that the IDs relocate to. We find that the market reactions of M&As in the provinces that IDs relocate to are more positive after the relocations, which suggests that distant IDs have an advisory role. Finally, we find that firms with more distant IDs have lower performance and that firms are less likely to reappoint IDs in future sessions if these IDs move farther away from the firm headquarters. Our study, based on exogenous changes in geographic distance between IDs and the firm headquarters, provides new evidence that IDs who are located farther from the firm headquarters are less effective monitors due to higher cost of information acquisition.